An Assessment of Facilities and Services Offer by Selected Modern Transport Companies of Peace and Young Shall Grow Mass Transit Limited in Ogoja Local Government Area and Their Implication to Tourism Development in Nigeria - Ajoma Simon Okwoche; Tawo Alfred Oyong; Odey Christopher Lifu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Transportation has been an integral part of tourism industry. A good surface transport system can improve tourism and better the economy of the nation as a whole. Thus, the qualities of facilities and service offer are prerequisites in modern transport companies for successful tourism development. Since transportation play a crucial role in tourism. Industry, a good surface transport system and qualities of service offer can bring a pull (motivation) of a tourist to embark on travel and tourism. Therefore the studies try to identify the various facilities and service offer by modern transport companies which can induce a tourist to use a particular transport company. Mixed method of qualitative and quantitative data collection was adjudged useful for the study 30 respondent were interview.